The use of Wayang-Based Media to Enhance Javanese Language Literacy among Madrasah Ibtidaiyah Students - Risyanti Risyanti; Joko Sulianto; Ngatmini Ngatmini (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study aims to describe the use of wayang media as a local culture-based strategy in improving the Javanese reading skills of second-grade students at MI Salafiyah Ngalian Tirto Pekalongan. This study is motivated by the low reading skills of students, especially in the aspects of pronunciation, fluency, intonation, and comprehension of reading content, so that concrete, interesting learning media are needed and are in accordance with the characteristics of elementary school students. This study uses a qualitative descriptive approach with a case study design with 66 research subjects, namely classes 2A and 2B. Data collection was carried out through observation, reading tests, interviews, and documentation during three meetings, while data analysis was carried out through data reduction, data presentation, and drawing conclusions using triangulation techniques. The results of the study indicate that the use of wayang media can create an active, fun, interactive, and contextual learning atmosphere. Students who learn using wayang media show a tendency to have better reading skills than students who learn without wayang media. Wayang media also increases students' attention, courage, participation, and enthusiasm in learning Javanese. Thus, wayang media can be an effective alternative learning media to improve Javanese reading skills while strengthening local cultural literacy in elementary school students.